2004
DOI: 10.1093/rpd/nch202
|View full text |Cite
|
Sign up to set email alerts
|

Novel developments in the MOSFET dosemeter for neutron dosimetry applications

Abstract: The feasibility of large-geometry Metal Oxide Semiconductor Field Effect Transistor (MOSFET) devices has been assessed for both active and passive neutron dosimetry and use in radiotherapy environments. Neutron sensitivity has been enhanced with the use of polymeric cement surrounding the gate region. Neutron activation via nuclear interaction processes is a potential problem with conventionally packaged and fabricated devices. To overcome this problem, a unique low-activation device design is described. Stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…They consist of a base metal layer of 5 of copper coated with a 3 layer of nickel and finally a 0.07 layer of gold. In later developments we intend to remove this gold layer to reduce any local dose-enhancement due to photoelectron generation at low energies [34].…”
Section: Description Of the Rectal Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…They consist of a base metal layer of 5 of copper coated with a 3 layer of nickel and finally a 0.07 layer of gold. In later developments we intend to remove this gold layer to reduce any local dose-enhancement due to photoelectron generation at low energies [34].…”
Section: Description Of the Rectal Arraymentioning
confidence: 99%
“…Device Linearity: Measurement of device linearity to absorbed radiation dose has shown that individual RadFETs follow a sufficiently linear model , at least up to approximately 50 Gy-absorbed dose (water), to allow simple determination of absorbed dose via a single calibration factor. This first-order model becomes increasingly inaccurate at higher levels of absorbed dose when it is more appropriate to use an exponential expression [34].…”
Section: Discusionmentioning
confidence: 99%
“…In individual monitorin, MOSFETs have been used mainly as gamma and neutron dosemeters (Kronenberg and Bruker, 1995;Lee et al, 2004;Price et al, 2004;Ravotti et al, 2005;Rosenfeld et al, 1995). The MOSFET itself is not significantly influenced by neutrons (Vettesse et al, 1996) and the response if any is mainly due to the interaction of neutrons with the packaging (Rosenfeld et al, 1995;Ravotti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The MOSFET itself is not significantly influenced by neutrons (Vettesse et al, 1996) and the response if any is mainly due to the interaction of neutrons with the packaging (Rosenfeld et al, 1995;Ravotti et al, 2005). However when covered with a converter it can be used as a neutron dosemeter (Kronenberg and Bruker, 1995;Lee et al, 2004;Price et al, 2004). Different converters have been applied in order to measure thermal and fast neutrons.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Recently, we a͒ Present address: Appleyard Lees, Halifax Office, 15 Clare Road, Halifax HX1 2HY, UK. b͒ have explored MOSFET applications in neutron dosimetry, 16 the statistical uncertainty in their response to x rays, 17 and the development of a linear MOSFET array for intracavatary in vivo dosimetry. 18 The process by which the MOSFET responds to radiation is well understood.…”
Section: Introductionmentioning
confidence: 99%